Measuring the financial health using the Altman Z-score model: A case study on listed banks in Bangladesh - Hasan, Md. Tamim; Ara, Rownok (Asian Journal of Economics and Empirical Research, 2025)
The study evaluates the financial performance of publicly listed banks in Bangladesh and forecasts potential financial distress using the Altman Z-score model. Based solely on secondary data from annual reports of the banks over the period 2018 to 2023, the analysis reveals alarming findings. Across the listed banks, 34 banks scored an average Z score of below the threshold level, placing them in the “Financial Distress Zone”, indicating a likelihood of financial difficulty or potential bankruptcy in the near future. Notably, 16 banks are not only scored below the threshold level and were placed in the financial distress zone but also recorded negative values, indicating a high risk of imminent financial collapsed. Only two banks namely Union Bank and Uttara Bank achieved average Z scores above the threshold level and were categorized in the “Grey Zone”, suggesting a reduced risk of financial distress in the short-term, though they should still remain conscious about their financial activities. The findings underscore the need for regulatory authorities to implement proactive measures to address financial instability within the banking sector. Additionally, the results offer valuable insights for bank managers, shareholders, investors, lenders, and customers to assess and mitigate financial risks, thereby contributing to informed decisions and promoting financial stability across the industry.